UNDERSTANDING OF SUSTAINABILITY REPORT: SEMIOTIC APPROACH - Zakhrani, Khaula Kharisma; Kamayanti, Ari (Jurnal Ilmiah Mahasiswa FEB, 2013)
The development of industrial sector is followed by increasing environment awareness. Along with that, company is not only obliged to make financial statement but also sustainability report. Sustainability report includes economic, social, and environmental condition of a company. This research presents an understanding of sustainability report from semiotic viewpoint. This research examines environmental aspect of Sustainability Report PT. Aneka Tambang Tbk, in 2011. Generally the research findings are divided into visual analysis and text analysis. The findings show that visual and textual appearances are supporting each other to create an image which is desired by the company. Sometimes, sustainability report becomes a tool for company to mask the reality. Â  Keywords: sustainability report, semiotic